LONG RUN COINTEGRATION IN ASEAN-4 STOCK MARKET: WHAT WE LEARNED? - Soegiarto, Eddy K; Reza, Faizal; Nurqamarani, Adisthy Shabrina (Archives of Business Research, 2019)
ASEAN-4 is an emerging market that experienced promising developed financial sector in recent years. The interaction between stock prices and macroeconomic variables has been extensively researched by researchers. By using secondary monthly ASEAN-4 data from January 2009 to December 2017 and using the ARDL estimation, it was found that exchange rates and GDP had a long-term positive effect on stock prices. While inflation, current account, and GDP have no effect on stock price formation. It is also found that there are co-integration in the short and long term in four ASEAN-4 countries. To strengthen the results of co-integration, using "one to one" interactions concluded that inflation, current accounts and interest rates have a very small contribution to the share price in ASEAN-4.